Atividades de retextualização entre oralidade e escrituralidade, um projeto para o 7º ano a partir de O Pequeno Príncipe - Santos, Maria Graça Manoela Pessoa dos (2018)
The present study is based on the theoretical-methodological tools of the Discursive Traditions model (Coseriu 1955/56, Koch 1997, Koch / Oesterreicher 1990, Kabatek 2006, Raible, among others). In this theoretical perspective, all discourse, whether it is transmitted phonic or graphically, is located in a space of the continuum of orality and scripturality (Koch / Oesterreicher 1990), which concerns not the medium of the texts, but to its discursive conception, this is, to its linguistic configuration. On the one hand, this work seeks to develop a didactic sequence (Dolz and Schneuwly 2004; Lopes-Rossi 2006) for the acquisition of scripturality (see Koch / Oesterreicher 1990) in the 7th. Year of Primary Education of a public school in Santa Maria (RN), based on the preparation and application of a guide for reading and producing texts on the work The Little Prince of Antoine de Saint Exupéry, with activities of re-contextualization (see Marcuschi 2005), which promote the displacement of texts in the continuity of orality and scripturality. On the other hand, it is sought to verify the impact of this intervention by analyzing the displacement of the productions of the different corpus groups (Diagnosis, First Rewriting, Final Version) in such a continuum. The analysis focuses on the junction techniques, understood as the expression of semantic relations (Raible 1992; Kabatek 2006; Castilho da Costa 2015). In the intervention phase of the project, the activities of retextualization promoted the students' contact with linguistic and TD varieties of the literary sphere, culminating in the production of a supplementary chapter to the literary work on canvas. In the analysis phase, we verified the quantitative and qualitative distribution of the join resources in the narratives of the corpus, that is, in relation to its frequency and the type of semantic relation and degree of syntactic integration. program Tradisc. As a result, the analysis showed a displacement of students' productions towards scripturality, proving the impact of the intervention for the acquisition and learning of the linguistic resources and traditionalities of the specific literaryness of the literary sphere.